2019
DOI: 10.1002/ange.201906709
|View full text |Cite
|
Sign up to set email alerts
|

The Case of Formic Acid on Anatase TiO2(101): Where is the Acid Proton?

Abstract: Carboxylic-acid adsorption on anatase TiO 2 is ar elevant process in many technological applications.Y et, despite several decades of investigations,t he acid-proton localization-either on the molecule or on the surface-is still an open issue.Bymodeling the adsorption of formic acid on top of anatase(101) surfaces,wehighlight the formation of ashort strong hydrogen bond. In the 0Klimit, the acid-proton behavior is ruled by quantum delocalization effects in asingle potential well, while at ambient conditions,t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Generally, the bidentate chelation mode, in which two oxygen atoms are coupled to the same Ti atoms, is considered the most stable mode compared to the other modes. [40][41][42] Therefore, in this work, we used the bidentate bridged mode to achieve optimal coupling in the dye@(TiO 2 ) 9 system (see Fig. S3, ESI †).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Generally, the bidentate chelation mode, in which two oxygen atoms are coupled to the same Ti atoms, is considered the most stable mode compared to the other modes. [40][41][42] Therefore, in this work, we used the bidentate bridged mode to achieve optimal coupling in the dye@(TiO 2 ) 9 system (see Fig. S3, ESI †).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Major features have been observed at around 1380 cm -1 and 1570 cm -1 that can be assigned to the symmetric stretch of O-C-O, ν s (COO), and the asymmetric stretch of O-C-O, ν a (COO), respectively. 45 Notably, in 2CuO, we have also observed peaks at 2920 cm -1 and 2850 cm -1 which can be assigned to C-H stretch, ν(C-H), and a combination band consisting of asymmetric O-C-O stretch and in-plane C-H bend, ν comb = ν a (COO) + 𝛿(C-H), as discussed by Hayden et al ν a (COO) + 𝛿(C-H) cannot be observed individually as they belong to the irreducible representation of C 2v , which can only be attributed to the bidentate adsorption configuration of FA in the form of formate (*HCOO) on the surface. [46][47][48] In 1CuO, from the absence of ν(C-H), the adsorption configuration can be assigned to carboxyl (*COOH) on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, since the experimental study of the wetting behaviors on surfaces with controllable molecular adsorption state is still challenging, molecular simulation is a promising tool for quantitatively investigating such systems. For example, the adsorption state of water on the TiO 2 surface is also a long-standing topic, which has been studied by numerous theoretical simulations. Selloni et al employed the first-principles calculations and molecular dynamics (MD) simulations to demonstrate that water molecules on various TiO 2 surfaces can adopt both dissociative adsorption (generated −OH groups) and molecular adsorption (in the H 2 O form) depending on the coverage. Furthermore, surface defects, environmental conditions, surface treatment, and UV radiation can strongly increase the proportion of dissociated adsorbed water on TiO 2 surfaces. , The adsorption of carboxylic acids has also been confirmed by some theoretical studies. According to these pioneer works, the hydrophilicity of TiO 2 is strongly affected by the species and adsorption state of surface molecules, and the adsorption of carboxylic acids could promote the self-cleaning effect of titanium dioxide. However, the quantitative relationship between the surface adsorption state and the wettability is still lacking, which might be the main reason for the debating of different wetting mechanisms of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%